COVID-19 and Civil Society in Southeast Asia: Beyond Shrinking Civic Space - Jasmin Lorch; Janjira Sombatpoonsiri (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2022)
In this article we challenge the conventional wisdom that COVID-19 and related legal restrictions invariably reinforce a global trend of shrinking civic space. We argue that the legal guarantee (or restriction) of civil society rights is not the sole factor configuring civic space. Instead, we reconceptualize civic space by broadening its determinants to also include needs-induced space and civil society activism. Investigating five countries with~flawed democracic or competitive autocracic regimes in Southeast Asia, we propose a three-pronged mechanism of how these determinants interact in the context of COVID-19. First, legal restrictions on civil society rights intertwine with the space created by health and economic needs to create new opportunities for civil society activism. Second, these new opportunity structures lead to the cross-fertilization between service delivery and advocacy activism~by civil society. Third, this new trajectory of civil society activism works to sustain civic space.
Keywords: 300; COVID-19; Shrinking space; Civic space; Civil society; Southeast Asia